The use of grafting to improve the net photosynthesis of cucumber - Esteves Amaro, Amanda Cristina [UNESP]; Macedo, Ana Claudia [UNESP]; Pereira Ramos, Anamaria Ribeiro [UNESP]; Goto, Rumy [UNESP]; Ono, Elizabeth Orika [UNESP]; Rodrigues, Joao Domingos [UNESP] (Brazilian Soc Plant Physiology, 2014)
Grafting induces significant changes in the growth and development of plants. Additionally, photosynthesis is directly proportional to light, and the stomatal aperture decreases with decreases in irradiance. The present study aimed to evaluate daily gas exchange rates and the response curve of the CO2 assimilation rate as a function of photosynthetic photon flux density in grafted and non-grafted Japanese cucumber plants with the objective of studying the underlying physiology. Two similar experiments were conducted in 2009 and 2010. The Japanese cucumber hybrid 'Taisho'was grafted on the pumpkin hybrid 'Excitte Ikki'using the tongue approach method. The results indicated that grafting affected photosynthetic metabolism. As a result of this metabolic change, the grafted plants had a higher net CO2 assimilation rate, a lower maximum quantum yield of photosynthesis and a higher transpiration rate than the non-grafted plants. Furthermore, the non-grafted plants appeared to be more sensitive to environmental conditions, as they showed a higher water use efficiency, indicating an improved water saving capability a lower saturation point of photosynthesis by light than the grafted plants. This result suggests that grafted plants tend to tolerate higher radiance levels than non-grafted plants.
Keywords: Cucumis sativus L.; Gas exchanges; Grafted plants; Light